Decrease of cardiovascular risk in patients with type 2 diabetes: review of the common strategies and clinical studies - Vladimir V. Salukhov (Endocrinology Research Centre, 2018)
Military Medical Academy of S.M. Kirov, Saint-Petersburg, Russia Recent clinical trials about the cardiovascular safety of empagliflozin and liraglutide demonstrated a convincing lowering effect on mortality from cardiovascular causes among the patients with type 2 diabetes. These findings resulted in many questions about why this phenomenon was seen in two drugs with widely different mechanisms of functioning. It is important to note that the glucose-lowering effect was moderate, although a feature seen in both empagliflozin and liraglutide was their ability to increase insulin sensitivity. In many fundamental studies, this feature was associated with a reduction of cardiovascular risks. Insulin resistance, which has always been a pathophysiological base for the development of cardiovascular disease in patients with type 2 diabetes, is a topic for this report. Different methods to manage insulin resistance, including lifestyle changes, drug treatment and metabolic surgery, are discussed. Furthermore, the most common features of glucose-lowering drugs are analysed, including protective effects for cardiovascular outcomes in patients with type 2 diabetes presented in randomised clinical trials. Studies include the United Kingdom Prospective Diabetes Study (UKPDS), PROspective pioglitAzone Clinical Trial In macroVascular Events (PROactive), Insulin Resistance Intervention After Stroke (IRIS), Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) and the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME). The current study shows that the potential to reduce the risk of cardiovascular disease is determined not only by effective lowering of glucose but also by the ability to lower insulin resistance, which causes a paradigm shift in the management of type 2 diabetes.